Notice of meeting
038-0123-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ACTING SECRETARY: J.H. MACALLUM SCOTT, ESQ. ASSISTANT SECRETARY: MISS M. MCDIAMID, B.A. 4, GREAT SMITH STREET, LONDON, S.W.1. TELEPHONE: ABBEY 2565 September 22, 1938. BASQUE CHILDREN'S COMMITTEE Please note that the next meeting of the Committee will be held at 14, Lord North Street, London, S.W.1 (by kind permission of Mrs. V. De Bunsen), on Tuesday, September 27th, at 4:00 P.M. 292/946/38/123